Investigating the binding behaviour of two avidin‐based testosterone binders using molecular recognition force spectroscopy. Issue 2 (10th January 2014) - Rangl, Martina; Leitner, Michael; Riihimäki, Tiina; Lehtonen, Soili; Hytönen, Vesa P.; Gruber, Hermann J.; Kulomaa, Markku; Hinterdorfer, Peter; Ebner, Andreas
<x xml:space="preserve">Abstract</x> Molecular recognition force spectroscopy, a biosensing atomic force microscopy technique allows to characterise the dissociation of ligand–receptor complexes at the molecular level. Here, we used molecular recognition force spectroscopy to study the binding capability of recently developed testosterone binders. The two avidin‐based proteins called sbAvd‐1 and sbAvd‐2 are expected to bind both testosterone and biotin but differ in their binding behaviour towards these ligands. To explore the ligand binding and dissociation energy landscape of these proteins, we tethered biotin or testosterone to the atomic force microscopy probe while the testosterone‐binding protein was immobilized on the surface. Repeated formation and rupture of the ligand–receptor complex at different pulling velocities allowed determination of the loading rate dependence of the complex‐rupturing force. In this way, we obtained the molecular dissociation rate (koff) and energy landscape distances (xβ) of the four possible complexes: sbAvd‐1‐biotin, sbAvd‐1‐testosterone, sbAvd‐2‐biotin and sbAvd‐2‐testosterone. It was found that the kinetic off‐rates for both proteins and both ligands are similar. In contrast, the xβ values, as well as the probability of complex formations, varied considerably. In addition, competitive binding experiments with biotin and testosterone in solution differ significantly for the two testosterone‐binding proteins, implying a decreased cross‐reactivity of sbAvd‐2. Unravelling the binding behaviour of the investigated testosterone‐binding proteins is expected to improve their usability for possible sensing applications. Copyright © 2014 John Wiley & Sons, Ltd.